Impak Amalan Wakaf Terhadap Pemerintahan Kerajaan ‘Uthmaniyyah di Bosnia & Herzegovina pada abad ke 15M hingga 17M: Waqf Impact towards Ottoman Reigns in Bosnia and Herzegovina during 15th to 17th Century - Alias, Nur Ainul Basyirah; Yahya, Shamsul Azhar; Rozali, Ermy Azziaty (Journal of Al-Tamaddun, 2023)
The Ottoman rule in the Balkan Peninsula began in the 14th century and lasted until the 19th century. However, there are also small provinces such as Serbia that demanded independence earlier while there are also other provinces that are still under the reign after the 19th century. Among the important elements in carrying out development in their territories is by implementing waqf practices in every aspect such as economy and socio-culture. Initially, these endowment institutions were mostly founded by the ruling class and those with high status in the local community. Through this establishment gave a great impact in the politics and government of the Ottoman government either from a positive or negative perspective. Therefore, this study aims to analyze the impact of waqf practices on the politics and rule of the ‘Ottomans in Bosnia & Herzegovina during the golden centuries of the kingdom, namely the 15th century to the 17th century. This study was conducted using qualitative methods in the form of historical research and collecting data using document analysis methods from various authoritative sources. The results of the study found that there were impacts on the practice of waqf in Bosnia & Herzegovina during that period. For example, it helped strengthen the power of the Ottoman even though not directly. This situation can be seen from the beginning of the practice of waqf through the involvement of Ottoman dignitaries who were from Bosnia, at the same time applying and integrating the Ottoman education system into the local community through waqf institutions that were built such as medrese. In addition, through the continuous development of waqf, it was able to stabilize the Ottoman rule in the region. This is because, the people see the government were able to prosper the economy for them while the Islamization process is becoming more and more vigorous due to the assistance from the cash waqf fund allocated for this activity. This led to an increase in the number of Muslims, making Islam the dominant religion in the region. In conclusion, the practice of waqf which is based on welfare and free services is not only considered to have an impact on community support but also can give a bad impression if it is not well managed by the government.